Pengaruh gaya kepemimpinan dan lingkungan kerja fisik terhadap karyawan PT Kalma Global Abyakta - Rakasiwi, Muhammad Nur Daffa; Handayani, Eva Mayfa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to analyze the influence of leadership style and the physical work environment on employee performance at PT Kalma Global Abyakta. The leadership style implemented by company leaders and the physical work environment are believed to play a significant role in shaping employee motivation, productivity, and performance achievement. The research method used was quantitative with a descriptive approach. Data were collected through questionnaires distributed to a number of respondents who were permanent employees of the company and analyzed using multiple linear regression techniques. The results indicate that leadership style and the physical work environment have a significant simultaneous and partial effect on employee performance. This finding emphasizes the importance of implementing an effective leadership style and creating a conducive physical work environment to improve human resource performance in the company. This study provides practical implications for the management of PT Kalma Global Abyakta in designing leadership strategies and improving work facilities.